A grounded theory of practice learning: What, and how, do students learn during practice placements and how can this learning be maximised? - Terri Grant; Yvonne Thomas (British Journal of Occupational Therapy, 2026)
Introduction: With ever increasing pressures on healthcare services and a rising demand for placement opportunities to enable the education and registration of greater numbers of healthcare professionals, it is vital that students gain maximum learning during placement opportunities. A grounded theory approach was used to explore what was learned and how the learning occurred during pre-registration occupational therapy programmes at one university in the UK’s West Midlands. This article presents and discusses a theory of practice learning developed during research with pre-registration occupational therapy students. Method: Eleven students and three practice educators participated in individual interviews following the first practice placement. Transcripts were analysed using constant comparison methods. Findings: The relationships between learning in four different categories previously reported were found to be interdependent and were further abstracted to develop a theory of practice learning that is characterised by the student’s availability for learning, which was impacted on and by each of the four categories and can be enhanced by actions taken by the student, the education establishment, and the practice educator. Conclusion: The theory of practice learning can be used to help students, practice educators and academics better understand and support student learning on placement.